Energy‐based predictive algorithm for semi‐active tuned mass dampers - Zelleke, Daniel H.; Matsagar, Vasant A. (The structural design of tall and special buildings, 2019)
Summary There are various control strategies proposed and implemented for the protection of structures against different types of dynamic excitations. Currently, semi‐active control devices are very popular due to their adaptability and low power requirement. In this paper, a novel energy‐based predictive (EBP) algorithm is proposed, and its effectiveness is studied when applied to semi‐active tuned mass damper (SATMD). The mechanical energy of the primary structure is taken as the key parameter to be used by the algorithm to predict a suitable value of the manipulated variable, the damping of the tuned mass damper (TMD). The choice of the damping is made such that the damping used at a time interval leads to the least possible mechanical energy of the primary structure. The efficacy of the proposed control algorithm is studied by employing the EBP algorithm on single‐story and multistory structures equipped with the SATMD. The performance of the proposed algorithm when applied to the SATMD is also compared with that with the passive TMD for similar parameters. The results of the study show that the implementation of the EBP algorithm leads to significantly reduced dynamic response as compared with the passive TMD. Furthermore, numerical studies are conducted to gain insight into the effect of various parameters such as the mass ratio, the TMD damping ratio, and the flexibility of the structure.